Inovasi Pembuatan Sabun Mandi Cair Dari Virgin Coconut Oil di Desa Tetangga UNSRI - Miksusanti Miksusanti; Zainal Fanani; Tri Kurnia Dewi; Desnelli Desnelli (Yayasan Literasi Sains Indonesia, 2023)
Community service has been conducted regarding counseling on making liquid soap from Virgin coconut oil. The service was carried out in front of mothers and young women in Semambu Island village. In the community service activities, demonstrations and practices are carried out on how to make liquid soap that smells good and can be used as bath soap from Virgin Coconut Oil. The community is very enthusiastic to learn how to make this soap because coconut raw materials are widely available in Semambu, Ogan Ilir Utara District, Jalan Raya Palembang-Prabumulih. Counseling and training on liquid soap are carried out face-to-face in the field. This activity was attended by 50 female recitation members as well as young women from the village. The activity was also attended by 7 Sriwijaya University students. The method of community service activities carried out is the delivery of scientific material and empirical facts from Island village. From the results of the activity, the participants tried to make their own soap using the raw materials provided by the community service team from the UNSRI Faculty of Mathematics and Natural Sciences.